2017
DOI: 10.1111/bjh.15004
|View full text |Cite
|
Sign up to set email alerts
|

What is currently known about the genetics of venous thromboembolism at the dawn of next generation sequencing technologies

Abstract: Summary Venous thromboembolism (VTE) has a strong genetic component. This review summarizes what is known at the seventeen genes that are now well established to harbour VTE‐associated genetic variants. In addition, it discusses additional candidate genes that deserve further validation before being claimed as VTE associated genes. Finally, several research strategies are briefly described to identify other molecular determinants of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 104 publications
1
39
0
1
Order By: Relevance
“…Two VTE associated loci, TSPAN15 and SLC44A2, increase also slightly the odds ratio for VTE (1.31 for TSPAN15 and 1.21 for SLC44A2, respectively) [32]. A comprehensive review about the genetics of VTE describing the allele prevalence and influence on VTE of various genetic variances was recently published [33]. The ThromboGenomics group in the United Kingdom using next generation sequencing and a high-throughput screening panel for genetic analysis of patients with coagulation, platelet or thrombotic disorders was able to identify a genetic diagnosis in 48.9% of patients with thrombotic disease [34].…”
Section: Inherited Thrombophiliamentioning
confidence: 99%
“…Two VTE associated loci, TSPAN15 and SLC44A2, increase also slightly the odds ratio for VTE (1.31 for TSPAN15 and 1.21 for SLC44A2, respectively) [32]. A comprehensive review about the genetics of VTE describing the allele prevalence and influence on VTE of various genetic variances was recently published [33]. The ThromboGenomics group in the United Kingdom using next generation sequencing and a high-throughput screening panel for genetic analysis of patients with coagulation, platelet or thrombotic disorders was able to identify a genetic diagnosis in 48.9% of patients with thrombotic disease [34].…”
Section: Inherited Thrombophiliamentioning
confidence: 99%
“…Despite the discovery of a region of interest on chromosome 3, no genes related to VT in previous GWAS studies were identified here . Are the SNPs identified in humans found in mice?…”
Section: The Questions Remainingmentioning
confidence: 81%
“…Some genetic variants that contribute to the risk have been identified in candidate genes, such as the factor V Leiden mutation. Other susceptibility single‐nucleotide polymorphisms (SNPs) have been identified in unsuspected genes, such as SLC44A2 or TSPAN15 , through high‐throughput genotyping strategies, mostly in genome‐wide association studies (GWASs) . However, even though those approaches have been successful in identifying new genes, much remains to be done to identify the missing heritability of VT, as known genetic variants explain only 5% of the heritability component.…”
mentioning
confidence: 99%
“…The field of exercise genomics is still in its early stages and characterized by underpowered and heterogeneous studies awaiting replication . Although we currently are not aware of any genetic variants related to CRF that have been identified in genome‐wide association studies of VTE, future adequately powered studies may investigate a potential causal association between CRF and VTE using a Mendelian randomization design …”
Section: Discussionmentioning
confidence: 99%